Comparison of HAV and HCV infections in vivo and in vitro reveals distinct patterns of innate immune evasion and activation - Colasanti, Ombretta; Burm, Rani; Huang, Hao-En; Riedl, Tobias; Traut, Jannik; Gillich, Nadine; Li, Teng-Feng; Corneillie, Laura; Faure-Dupuy, Suzanne; Grünvogel, Oliver; Heide, Danijela; Lee, Ji Young; et al. (Journal of hepatology, 2023)
Background & Aims - Hepatitis A virus (HAV) infections are considered not to trigger innate immunity in vivo, in contrast to hepatitis C virus (HCV). This lack of induction has been imputed to strong interference by HAV proteases 3CD and 3ABC. We aimed to elucidate the mechanisms of immune activation and counteraction by HAV and HCV in vivo and in vitro. - Methods - Albumin-urokinase-type plasminogen activator/severe combined immunodeficiency (Alb/uPA-SCID) mice with humanised livers were infected with HAV and HCV. Hepatic cell culture models were used to assess HAV and HCV sensing by Toll-like receptor 3 and retinoic acid-inducible gene I/melanoma differentiation-associated protein 5 (RIG-I/MDA5), respectively. Cleavage of the adaptor proteins TIR-domain-containing adapter-inducing interferon-β (TRIF) and mitochondrial antiviral-signalling protein (MAVS) was analysed by transient and stable expression of HAV and HCV proteases and virus infection. - Results - We detected similar levels of interferon-stimulated gene induction in hepatocytes of HAV- and HCV-infected mice with humanised liver. In cell culture, HAV induced interferon-stimulated genes exclusively upon MDA5 sensing and depended on LGP2 (laboratory of genetics and physiology 2). TRIF and MAVS were only partially cleaved by HAV 3ABC and 3CD, not sufficiently to abrogate signalling. In contrast, HCV NS3-4A efficiently degraded MAVS, as previously reported, whereas TRIF cleavage was not detected. - Conclusions - HAV induces an innate immune response in hepatocytes via MDA5/LGP2, with limited control of both pathways by proteolytic cleavage. HCV activates Toll-like receptor 3 and lacks TRIF cleavage, suggesting that this pathway mainly contributes to HCV-induced antiviral responses in hepatocytes. Our results shed new light on the induction of innate immunity and counteraction by HAV and HCV. - Impact and Implications - Understanding the mechanisms that determine the differential outcomes of HAV and HCV infections is crucial for the development of effective therapies. Our study provides insights into the interplay between these viruses and the host innate immune response in vitro and in vivo, shedding light on previously controversial or only partially investigated aspects. This knowledge could tailor the development of new strategies to combat HCV persistence, as well as improve our understanding of the factors underlying successful HAV clearance.